Some strategic aspects of animal protein production - Horn, Péter (Acta Agraria Debreceniensis, 2018)
The access to food shaped human societies and dietary models throughout the history of mankind. Animal protein consumption became a part of human culture. Data are presented showing the relationship of daily calorie and animal protein consumption as affected by capita GDP changes. Examples are presented how genetic improvement of animal and fodder plants influenced the resource efficiency and the overall environmental footprint per unit product. The two examples presented are: the dairy industry of the USA the 1944 and 2007 situation, and the Hungarian broiler chicken sector considering data relevant to 1930, 1960 and 2010. In both cases, dramatic improvements in resource efficiency could be demonstrated. The agricultural area required to animal feed production was reduced by more than 80% in both cases per unit product. Future possibilities are briefly discussed, referring to the still unutilized land reserves of the Globe, the new evolving technologies in progress inclusive the CASPR/Cas 9 genetic editing methods.